Seminario internacional de ingeniería oceánica - Grijalva López, Luis Pablo; Bustamante Ahumada, Roberto (My University, 1982)
Wind generated surface water waves are of major importance to design, operation and safety of marine structures. Estimates of hazards for loss of human life and for pollution of the marine environment require good descriptions of ocean winds, waves and currents.
Keywords: costa afuera; ambiente marino; dunas; barras; arrastre; geofísica marina; escolleras